Determinación del daño de Babosa (Gasteropoda: Limacidae) en el cultivo de Arroz (Oryza sativa L.), variedad Capirona, bajo condiciones Semicontroladas en el Bajo Mayo - Tarapoto. - Jiménez Gálvez, Lila Esperanza (2004)
The present work was realized in the dístrict of Tarapoto (province of San Martin) at 368 m. above see level. The mean temperature is about 28º C and the precipitation 1200mmlyear. The aim of this work was the evaluation of the foliar damages caused by slug on rice plants (Oryza sativa), Capirona variety, planted in 0.1194m2 pots. The slugs (Gasteropoda: Limacidae) were released according to the different densities: 0.1; 02; 0.4; O.B; 1.6; 3.2; G.4 slug/ shoot. These densities were compared with the witness {O slug/ shoot).The infestation of the experimental units were done 40 days after germination en the sprouting stage (phenological stage 2}. We used the model of divided parcels (plots) with 32 experimental units. The parcels were divided with half of each constituted by young leaves and the other half by old leaves. Evaluations were recorded every five days. En terms of incidence and severity, the results showed that highest densities caused damages to young leaves but not to old leaves. In conclusion the densities of 0.1; 02; 0.4; O.B; 1.6; 3.2; 6.4 slug/ shoot occasioned a foliar damage of 19.60; 13.90; 22.40; 31 .70; 42.20; 57.00 and 67.50 percent. However, growth and performance were not affected by the level of 01 to 6.4 slugs per shoot.